Cooking methods affect advanced glycation end products and lipid profiles: A randomized cross-over study in healthy subjects - Wellens, Judith; Vissers, Eva; Dumoulin, Anaïs; Hoekx, Sien; Vanderstappen, Julie; Verbeke, Joke; Vangoitsenhoven, Roman; Derrien, Muriel; Verstockt, Bram; Ferrante, Marc; Matthys, Christophe; Raes, Jeroen; et al. (Cell reports. Medicine, 2025)
Thermal treatments used in ultra-processed foods (UPFs) lead to advanced glycation end products (AGEs). UPFs and serum AGEs are associated with cardiometabolic disease. We explore differential cooking methods as a mechanistic link between UPFs and detrimental health outcomes through a randomized cross-over cooking method trial in healthy subjects using identical ingredients and a deep profiling analysis. We show that low-AGE-generating cooking methods such as boiling and steaming decrease serum AGEs, improve lipid profiles, and increase serum protein 4E-BP1. In contrast, high-AGE-generating cooking methods such as grilling and baking increase fecal butyrate. In sum, this suggests that low-AGE-generating cooking methods should be considered in cardiovascular risk prevention. Since current dietary guidelines focus on ingredients, but not cooking methods, our results suggest that culinary techniques should be considered as an important factor in cardiometabolic preventive strategies and future dietary trial design. This study was registered at ClinicalTrials.gov (NCT06547190). [Display omitted] •Cooking methods alter food’s biological impact, even with identical ingredients•Boiling and steaming improve lipid profiles and increase serum protein 4E-BP1•Grilling and baking increase advanced glycation end products and fecal butyrate•Culinary techniques should be considered in cardiometabolic preventive strategies Wellens et al. explore the effects of cooking methods that generate differential levels of advanced glycation end products (AGEs) in food on human health. They suggest that low-AGE-generating cooking methods should be considered in cardiovascular prevention strategies and dietary trial design.